The relationship of visual preference for Chinese traditional village landscape with perceived values and functions - Liang, Nian Long; Maulan, Suhardi; Mohd Yusof, Mohd Johari; Abu Bakar, Shamsul (Asian Scholars Network, 2023)
The sustainable development of traditional village landscape is not only crucial to the inheritance of China's millennium farming culture, but also indicators to the success or China's rural revitalization strategy. However, the policy and strategy for traditional village policy development is top-down approach in nature and it is argued that the development policies have not been effectively implemented resulted to the Chinese traditional villages undergone extraordinary changes. The reason for this phenomenon may be due to the situation that the policy is formulated without taking into consideration of local residents’ needs. Thus, this study intent to explored the relationship between local residents' perceived values and functions and their visual preferences for traditional village landscapes, in order to guide planners and decision-makers for more sustainable development policies and strategies which is consistent with local residents. The survey results of 400 numbers of participants at Guilin for visual preferences show that the local residents mostly prefer the mixed village landscape on the premises of retaining the traditional characteristics of the traditional elements but at the same time able to integrate the needs for modern living style. For the local residents' recognition of the traditional village landscape values and functions, the results also show that the local residents have the highest agreement on the ecological functions of traditional village landscapes. However, local residents have the lowest agreement on the economic value of traditional village landscapes. It is also found that perceived ecology function have the greatest effect on visual preferences for mixed style. Based on the findings, it is suggested that the principle of ecological priority rather than excessive development should be followed in the conservation and development of traditional village landscapes which emphasized on the combination of traditional and modern elements to meet people's needs for high-quality life.